Improving Teachers' Skills in Digital Literacy through Workshops at SD Negeri Trayu Kapanewon Samigaluh, Kulon Progo Regency in the 2022/2023 Academic Year - Asih, Asih (IJCER (International Journal of Chemistry Education Research), 2024)
The purpose of the study was to determine the ability of teachers to use digital literacy with aspects of Internet Searching and Knowledge Assembly, and to determine the ability of researchers to manage workshops. The research method used in this study is school action research using three cycles, each cycle consisting of planning, implementation, observation, and reflection. The subject of this research is the teachers of SD Negeri Trayu Kapanewon Samigaluh Kulon Progo Regency, totalling 8 people consisting of 6 class teachers and 2 subject teachers. Data collection using qualitative data and quantitative data. Observation sheets were used to collect data on the use of digital literacy and workshop management data. The results showed that at the stage of lesson planning by teachers as a whole, the total number received an average score of 2.46 with an unsatisfactory predicate, then at the implementation stage, the average result was 2.24; with a less good category. Furthermore, on the teacher's ability to use digital literacy as a learning resource which includes aspects of Internet Searching and aspects of Knowledge Assembly, as well as on its implementation, the average result is 4.35 with a very skilled category.